Prince Ricardo of Pantouflia: Being the Adventures of Prince Prigio's Son - Lang, Andrew, 1844-1912; Browne, Gordon, 1858-1932 (Salt Lake City, UT : Project Gutenberg, 2007)
"Prince Ricardo of Pantouflia: Being the Adventures of Prince Prigio's Son" by Andrew Lang is a fantasy novel likely written in the late 19th century. This whimsical tale follows Prince Ricardo, the son of the clever Prince Prigio, as he embarks on his own adventures filled with magical elements and moral lessons. The story addresses themes of growth, courage, and the importance of intellect over mere physical prowess, all while delivering a blend of humor and charm befitting a fairy tale. The opening of the story introduces us to King Prigio and Queen Rosalind, who express concern over their son's reckless and adventure-seeking behavior, contrasting with their hopes for his education. As they discuss the influences of fairy tales on Ricardo's upbringing, the narrative hints at his inclination to avoid studying in favor of mythical exploits. In a series of light-hearted exchanges, we learn of his recent escapades, including rescuing a princess from a sea monster, and the expectations placed on him due to his lineage. The stage is set for his forthcoming adventures, marked by the dynamics of father-son relationships and the looming question of how each character$1 (Bs strengths will shape their fates. (This is an automatically generated summary.)s
Release date is 2007-07-04
Transcribed from the 1893 J. W. Arrowsmith edition by David Price
Keywords: Fairy tales; Children's stories